Secure transmission scheme for millimeter-wave Internet of vehicles with multiple base stations and users - JU Ying; CHEN Yuchao; TIAN Suheng; LIU Lei; LI Zan; PEI Qingqi; WANG Mingyang (Tongxin xuebao)
For the timeliness of millimeter-wave secure beamforming in mobile scenarios and the robustness of secure connections in millimeter-wave dynamic eavesdropping scenarios, a multi-agent secure cooperative communication scheme based on a dueling double deep Q network (D3QN)-deep deterministic policy gradient (DDPG) algorithm was proposed to address communication security issues. The scheme utilized road side unit (RSU)-assisted cooperative jamming technology to reduce the eavesdropper’s reception quality of confidential signals. The optimization problem was formulated to maximize the total secrecy rate of all legitimate vehicles by optimizing the joint base station and beam connection control of the VUs, the selection of the jamming RSUs, and the cooperative jamming direction and transmit power of RSUs. Furthermore, for the challenges posed by the high dynamics of vehicular networks, the scheme achieved a fusion of real-time discrete and continuous decision-making by creating a VU agent grounded in D3QN and an RSU agent harnessing D3QN-DDPG capabilities. Finally, through multi-dimensional performance analysis and scheme comparison experiments, simulation results demonstrate the effectiveness of the proposed scheme.